Factors impacting the interactions of engineered nanoparticles with bacterial cells and biofilms: Mechanistic insights and state of knowledge. (1st November 2018) - Joo, Sung Hee; Aggarwal, Srijan
Abstract: Since their advent a few decades ago, engineered nanoparticles (ENPs) have been extensively used in consumer products and industrial applications and their use is expected to continue at the rate of thousands of tons per year in the next decade. The widespread use of ENPs poses a potential risk of large scale environmental proliferation of ENPs which can impact and endanger environmental health and safety. Recent studies have shown that microbial biofilms can serve as an important biotic component for partitioning and perhaps storage of ENPs released into aqueous systems. Considering that biofilms can be one of the major sinks for ENPs in the environment, and that the field of biofilms itself is only three to four decades old, there is a recent and growing body of literature investigating the ENP-biofilm interactions. While looking at biofilms, it is imperative to consider the interactions of ENPs with the planktonic microbial cells inhabiting the bulk systems in the vicinity of surface-attached biofilms. In this review article, we attempt to establish the state of current knowledge regarding the interactions of ENPs with bacterial cells and biofilms, identifying key governing factors and interaction mechanisms, as well as prominent knowledge gaps. Since the context of ENP-biofilm interactions can be multifarious—ranging from ecological systems to water and wastewater treatment to dental/medically relevant biofilms— and includes devising novel strategies for biofilm control, we believe this review will serve an interdisciplinary audience. Finally, the article also touches upon the future directions that the research in the ENP-microbial cells/biofilm interactions could take. Continued research in this area is important to not only enhance our scientific knowledge and arsenal for biofilm control, but to also support environmental health while reaping the benefits of the 'nanomaterial revolution'. Highlights: Hydrophobicity and aggregation of engineered nanoparticles (ENPs) affect toxicity. ENP-biofilm interactions are less studied than ENP-bacterial interactions. ENPs may significantly partition to natural biofilms in aquatic systems. Disintegration of extracellular polymeric substance (EPS) could remove biofilms. ENPs may inhibit biofilms by interfering with quorum sensing.